Chronic prostatitis/pelvic pain syndrome: MRI findings and clinical correlations. (2nd July 2019) - Clemente, Alfredo; Renzulli, Matteo; Reginelli, Alfonso; Bellastella, Giuseppe; Brusciano, Luigi; Biselli, Maurizio; Schiavina, Riccardo; Golfieri, Rita; Cappabianca, Salvatore
Abstract: We aimed to evaluate whether pelvic magnetic resonance imaging (MRI) could play a role in better assessing chronic pelvic pain syndrome. We evaluated 44 male patients (median 41 aged) with a clinical history of painful pelvic symptoms, lasting for at least three of the previous 6 months, associated with urinary, anorectal and sexual disorders in the absence of bacterial prostate infection. All these patients underwent ultrasound (US) and MRI evaluation of the pelvis. Prostate imaging findings, such as gland morphology evaluated by US and prostatic signal intensity on MRI, appeared normal in the majority of patients (38/44; 82%). Extraparenchymal alterations were found in 28 patients (63.6%); the most frequent was the dilatation of periprostatic vein plexus (20/28; 71.4%), significantly correlated to chronic pelvic pain syndrome ( p  = 0.0013), regardless of different clinical presentations. This finding was tested in a control group of 90 patients, demonstrating an excellent specificity (97%), good positive predictive value (87%) and diagnostic accuracy (80%). MRI confirmed its high capability in evaluating prostatic and extraprostatic structures. Periprostatic vein dilatation, which identified approximately two‐thirds of the patients with chronic pelvic pain syndrome using pelvic MRI, significantly correlated to chronic pelvic pain syndrome, independently of patient age, symptoms and prostatic volume.